State-Owned Enterprise Performance: Characteristics Of Good Female Directors In Indonesia - Widiasmara, Anny; Sudrajat, M. Agus (Politeknik Negeri Madiun, 2025)
This study empirically examines the influence of female directors’ characteristics, political connections, educational background in economics or business, and education level on the performance of Indonesian State-Owned Enterprises (BUMN). These factors are crucial as they affect strategic quality impacting BUMN performance. Regulation PER-8/MBU/08/2020 encourages increasing female representation on boards. The study measures BUMN performance comprehensively across financial, administrative, and operational dimensions, reflecting their dual role as public servants and state profit generators. Using a quantitative approach, the sample includes all BUMNs with female directors from 2018 to 2023. Data were sourced from IDX, company websites, annual and financial reports, and the Ministry of BUMN’s documentation (PPID). Data analysis employed SPSS version 25. Findings reveal political connections significantly influence BUMN performance, while female directors’ characteristics, education background, and education level show no significant effect, likely due to limited strategic decision-making roles for women. Directors with political ties can offer strategic advantages but require balanced transparency and accountability.The study’s novelty lies in its comprehensive integration of female director traits, political connections, and education with multi-dimensional BUMN performance measures. It also evaluates BUMN’s dual function amid board restructuring policies, providing updated empirical insights on the impact of increasing women on BUMN boards